Fe3O4@TiO2 Microspheres: Harnessing O2 Release and ROS Generation for Combination CDT/PDT/PTT/Chemotherapy in Tumours - Bo Zhao; Xiuli Hu; Lu Chen; Xin Wu; Donghui Wang; Hongshui Wang; Chunyong Liang (Nanomaterials, 2024)
In the treatment of various cancers, photodynamic therapy (PDT) has been extensively studied as an effective therapeutic modality. As a potential alternative to conventional chemotherapy, PDT has been limited due to the low Reactive Oxygen Species (ROS) yield of photosensitisers. Herein, a nanoplatform containing mesoporous Fe3O4@TiO2 microspheres was developed for near-infrared (NIR)-light-enhanced chemodynamical therapy (CDT) and PDT. Titanium dioxide (TiO2) has been shown to be a very effective PDT agent; however, the hypoxic tumour microenvironment partly affects its in vivo PDT efficacy. A peroxidase-like enzyme, Fe3O4, catalyses the decomposition of H2O2 in the cytoplasm to produce O2, helping overcome tumour hypoxia and increase ROS production in response to PDT. Moreover, Fe2+ in Fe3O4 could catalyse H2O2 decomposition to produce cytotoxic hydroxyl radicals within tumour cells, which would result in tumour CDT. The photonic hyperthermia of Fe3O4@TiO2 could not only directly damage the tumour but also improve the efficiency of CDT from Fe3O4. Cancer-killing effectiveness has been maximised by successfully loading the chemotherapeutic drug DOX, which can be released efficiently using NIR excitation and slight acidification. Moreover, the nanoplatform has high saturation magnetisation (20 emu/g), making it suitable for magnetic targeting. The in vitro results show that the Fe3O4@TiO2/DOX nanoplatforms exhibited good biocompatibility as well as synergetic effects against tumours in combination with CDT/PDT/PTT/chemotherapy.